Into Space - A Journey of How Humans Adapt and Live in Microgravity 2018
DOI: 10.5772/intechopen.77214
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cells in Microgravity

Jun Chen

Abstract: The excessive proliferation and metastasis of tumor cells are due to frequent genetic alterations and subsequent stimulation of abnormal signal transduction pathways. Inventing and improving novel therapeutic strategies are critically needed. However, it remains unknown which of these pathways is essential to tumor initiation and progression. A weightless environment on Earth is a rare phenomenon, achieved using various simulations, but brings about changes of internal cellular structure and interactions among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Furthermore, EMT is also involved in other steps in the cancer process. Under microgravity, the TGF- β signaling pathway simultaneously inhibits the expression of two EMT-induced genes, snail1 and snail2 , and promotes apoptosis [ 20 , 21 ].…”
Section: The Effect Of Microgravity On the Biological Behavior Of The Cancer Cellmentioning
confidence: 99%
“…Furthermore, EMT is also involved in other steps in the cancer process. Under microgravity, the TGF- β signaling pathway simultaneously inhibits the expression of two EMT-induced genes, snail1 and snail2 , and promotes apoptosis [ 20 , 21 ].…”
Section: The Effect Of Microgravity On the Biological Behavior Of The Cancer Cellmentioning
confidence: 99%
“…In addition, s-µ g attenuated the expression of integrin-β1 and integrin-β4 and affected adhesion signaling by decreasing FAK, PYK2, and ILK kinase activity in MCF-7 cells [ 72 ]. Chen [ 90 ] later proposed that both decreased integrin expression and downregulated FA kinase activities are key processes in suppression of breast cancer cell migration under s-µ g . Most recently, Shi et al [ 91 ] performed experiments with MCF-7 cells on an RWV and reported that EMT transcription factors (Snail, Twist, and ZEB1) are also involved in the alteration of cell adhesion properties under s-µ g .…”
Section: Breast Cancer Cells Exposed To Microgravitymentioning
confidence: 99%
“…Space experiments are of great value for the study of various physiological characteristics of the human body; health problems; and, in particular, cancer [1][2][3]. Microgravity allows one to explore the molecular and cellular mechanisms of the biological effects on cellular stress and the transformation of normal and tumor cells with a change in gravity [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have indicated that simulated microgravity affects cellular morphology, proliferation, apoptosis, invasion, and migration while inhibiting cancerous cell growth and invasion [6][7][8][9][10][11][12][13]. After simulated-microgravity exposure, apoptosis has been observed in glial cells [7], endothelial cells [8], thyroid cancer cells [9], and Jurkat cells [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation